Promoting the Use of Critical Discourse Analysis (CDA) to Evaluate ESP Textbooks - Munir, Ahmad; Seswanto (IJET (Indonesian Journal of English Teaching), 2025)
Since English has become a professional and communication language in various domains in Indonesia, it is necessary to take into consideration a variety of English used in specific domains, which is called English for Specific Purposes (ESP). To accommodate the instructional material, ELT textbooks have a vital role due to their authority to strengthen teachers’ identity. By employing critical discourse analysis (CDA), teachers can critically evaluate ESP textbooks to ensure they are not just linguistically correct but also culturally sensitive, professionally relevant, and ideologically sound, thereby improving the overall efficacy of ESP instruction. Thus, it is believed that ESP textbook evaluation using CDA is an important thing to do. This article aims at promoting CDA to evaluate textbooks especially ESP. This approach fosters continuous improvement in teaching practices and curriculum development, ultimately enhancing the educational experience for learners in specialized fields. This paper provides the readers with detail explanations about the importance of textbook evaluation, the basic concepts of CDA, the roles of CDA in evaluating ESP textbooks and steps in evaluating ESP textbooks using CDA. In this paper, suggestions and recommendations are also offered to the ESP teachers, students, stakeholders, policymakers, and curriculum developers to use CDA to evaluate ESP textbooks.